Precalculus (10th Edition)

Published by Pearson
ISBN 10: 0-32197-907-9
ISBN 13: 978-0-32197-907-0

Chapter 11 - Systems of Equations and Inequalities - Chapter Review - Cumulative Review - Page 797: 4



Work Step by Step

$9^{x+1}=(3^2)^{x+1}=3^{2(x+1)}=3^{2x+2}$, hence the equation becomes: $3^{x}=3^{2x+2}$. We know that if $a\ne1,-1$, then $a^k=a^l\longrightarrow k=l$. Hence: $2x+2=x\\(2x+2)-x=x-x\\x+2=0\\(x+2)-2=0-2\\x=-2.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.